2000
DOI: 10.1001/jama.284.8.978
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Administration of Hepatitis B Vaccine at Birth and Completion of the Hepatitis B and 4:3:1:3 Vaccine Series

Abstract: Administration of the first dose of hepatitis B vaccine at birth is associated with increased likelihood of completion of the hepatitis B vaccination series. JAMA. 2000;284:978-983

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
54
0

Year Published

2001
2001
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(57 citation statements)
references
References 15 publications
1
54
0
Order By: Relevance
“…Also, completion of the hepatitis B vaccination series is more likely among those receiving the first dose at birth. 22 Midwives in this study had overall confidence in the neonatal hepatitis B vaccine's safety, although more than one-third believed that the vaccine was given too young. In addition, their concern about concurrent immunisation has implications for how midwives would support additions to the infant schedule.…”
Section: Discussionmentioning
confidence: 77%
“…Also, completion of the hepatitis B vaccination series is more likely among those receiving the first dose at birth. 22 Midwives in this study had overall confidence in the neonatal hepatitis B vaccine's safety, although more than one-third believed that the vaccine was given too young. In addition, their concern about concurrent immunisation has implications for how midwives would support additions to the infant schedule.…”
Section: Discussionmentioning
confidence: 77%
“…12 Hepatitis B vaccination in the hospital increases the likelihood that a child will complete the recommended 3-dose hepatitis B vaccine series. 13 Also, beginning with the 2002 harmonized immunization schedule, approved by the ACIP, AAP, and the American Academy of Family Practitioners, a preference is stated for the first dose to be administered soon after birth. 14 The overall 76.2% infant hepatitis B vaccination rate seen in this study is slightly lower than the 81% found in a 1996 survey (New Hampshire unpublished data 1996).…”
Section: Discussionmentioning
confidence: 99%
“…17 Apart from providing early protection against the establishment of HBV infection in infants, the use of a birth dose has been associated with increased rates of individuals who actually complete the vaccination schedule. 18,19 Furthermore, an early booster dose between 4-5 years may increase the number of children with sero-protection. 16 Since the introduction of HBV vaccination in the EPI programme in 2002 in Ghana, few studies to evaluate the development of sero-protection against HBV infections in infants have been done 11,20 , and the manufacturers of the supply of vaccines have been changed a number of times.…”
Section: Introductionmentioning
confidence: 99%